The Use of Quinacrine in Nitroimidazole-resistant Giardia Duodenalis: An Old Drug for an Emerging Problem. (6th February 2017) - Requena-Méndez, Ana; Goñi, Pilar; Rubio, Encarnación; Pou, Diana; Fumadó, Victoria; Lóbez, Silvia; Aldasoro, Edelweiss; Cabezos, Juan; Valls, Maria Eugenia; Treviño, Begoña; Martínez Montseny, Antonio Federico; Clavel, Antonio; et al.
Summary: The study describes an almost 20% prevalence of imported refractory giardiasis diagnosed in 3 Tropical-Medicine Units in Barcelona, shows a 100% efficacy rate of quinacrine in nitroimidazole-refractory cases, and compares genetic characteristics of Giardia cases. Abstract: Background: There is little evidence regarding the management of refractory giardiasis after treatment with nitroimidazoles. This study estimates the proportion of persistent giardiasis in 3 hospitals in Barcelona, describes associated risk factors and genotype, and evaluates the efficacy rate of quinacrine in those with persistent giardiasis. Methods: A clinical, prospective, observational study was conducted in patients with giardiasis treated with nitroimidazoles. Those with persistent giardiasis were provided quinacrine. Molecular characterization of Giardia isolates was performed by polymerase chain reaction amplification of a fragment of tpi and bg genes. Results: Seventy-seven patients were recruited and treated with nitroimidazoles, and in 14 of 71 (20%) of patients followed up, Giardia persisted. Refractory giardiasis was associated with malaise ( P = .007) and anorexia ( P = .02), with previous giardiasis ( P = .03), and with previous antibiotic ( P = .02) or antiparasitic( P = .04) use. Quinacrine had an effectiveness rate of 100% in refractory giardiasis (n = 13; 95% confidence interval = 75–100). Molecular characterization showed that 17 (25%) Giardia isolates belonged to assemblage A, and 31 (43%) belonged to assemblage B. In refractory giardiasis, assemblage A and B were found responsible in 4 and 6 cases, respectively. Conclusions: Almost 20% of patients presented persistent giardiasis, belonging to both assemblages A and B, after nitroimidazole. Short course of quinacrine was effective in treating refractory cases. Further controlled studies should evaluate its efficacy and safety.